x2 + 5x - 6
= x2 - x + 6x - 6
= (x2 - x) + (6x - 6)
= x(x - 1) + 6(x - 1)
= (x + 6)(x - 1)
= x2-x +6x-6 = x(x-1)+6(x-1)=(x+6)(x-1)
\(x^2+5x-6\)
<=> \(\left(x^2-x\right)+\left(6x-6\right)\)
<=> x(\(\left(x-1\right)+6\left(x-1\right)\)
<=> \(\left(x-1\right)\left(x+6\right)\)
Nhớ tích cho mình nhé
\(x^2+5x-6=x^2+5x-1-5\)
\(=\left(x^2-1\right)+5\left(x-1\right)\)
\(=\left(x-1\right)\left(x+1\right)+5\left(x-1\right)\)
\(=\left(x-1\right)\left(x+1+5\right)\)
\(=\left(x-1\right)\left(x+6\right)\)
x\(^2\) + 5x - 6
= x\(^2\) - x + 6x - 6
= (x\(^2\) - x) + (6x - 6)
= x(x - 1) + 6(x - 1)
= (x + 6)(x - 1)
\(x^2+5x-6=x^2-x+6x-6\)
\(=x\left(x-1\right)+6\left(x-1\right)=\left(x-1\right)\left(x+6\right)\)
x2 + 5x - 6
= x2 - x + 6x - 6
= (x2 - x) + (6x - 6)
= x(x - 1) + 6(x - 1)
= (x + 6)(x - 1)